Rho and Rab Small G Proteins Coordinately Reorganize Stress Fibers and Focal Adhesions in MDCK Cells - Imamura, Hiroshi (The American Society for Cell Biology, 1998)
The Rho subfamily of the Rho small G protein family (Rho) regulates formation of stress fibers and focal adhesions in many types of cultured cells. In moving cells, dynamic and coordinate disassembly and reassembly of stress fibers and focal adhesions are observed, but the precise mechanisms in the regulation of these processes are poorly understood. We previously showed that 12-O-tetradecanoylphorbol-13-acetate (TPA) first induced disassembly of stress fibers and focal adhesions followed by their reassembly in MDCK cells. The reassembled stress fibers showed radial-like morphology that was apparently different from the original. We analyzed here the mechanisms of these TPA-induced processes. Rho inactivation and activation were necessary for the TPA-induced disassembly and reassembly, respectively, of stress fibers and focal adhesions. Both inactivation and activation of the Rac subfamily of the Rho family (Rac) inhibited the TPA-induced reassembly of stress fibers and focal adhesions but not their TPA-induced disassembly. Moreover, microinjection or transient expression of Rab GDI, a regulator of all the Rab small G protein family members, inhibited the TPA-induced reassembly of stress fibers and focal adhesions but not their TPA-induced disassembly, indicating that, furthermore, activation of some Rab family members is necessary for their TPA-induced reassembly. Of the Rab family members, at least Rab5 activation was necessary for the TPA-induced reassembly of stress fibers and focal adhesions. The TPA-induced, small G protein-mediated reorganization of stress fibers and focal adhesions was closely related to the TPA-induced cell motility. These results indicate that the Rho and Rab family members coordinately regulate the TPA-induced reorganization of stress fibers and focal adhesions that may cause cell motility.